Dynamic wetting of a fluoropolymer surface by ionic liquids - Li, H.; Sedev, Rossen; Ralston, J. (R S C Publications, 2011)
The spontaneous spreading of ionic liquids on a fluoropolymer surface (Teflon AF1600) in air is investigated by high-speed video microscopy. Six ionic liquids (EMIM BF4, BMIM BF4, OMIM BF4, EMIM NTf2, BMIM NTf2 and HMIM NTf2) are used as probe liquids. The dependence of the dynamic contact angle on contact line velocity is interpreted with a hydrodynamic model and a molecular-kinetic model. The usefulness of the hydrodynamic model is rather limited. There is a good correspondence between the molecular dimensions of the liquids and the physical parameters of the molecular-kinetic model. The viscous and molecular-kinetic contributions to energy dissipation are calculated, revealing that energy is dissipated in the bulk as well as at the contact line during dynamic wetting. There are wide ramifications of these results in areas ranging from lubrication and biology to minerals processing and petroleum recovery.